2004
DOI: 10.1523/jneurosci.1974-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Stretch Growth of Integrated Axons

Abstract: Large animals can undergo enormous growth during development, suggesting that axons in nerves and white matter tracts rapidly expand as well. Because integrated axons have no growth cones to extend from, it has been postulated that mechanical forces may stimulate axon elongation matching the growth of the animal. However, this distinct form of rapid and sustained growth of integrated axons has never been demonstrated. Here, we used a microstepper motor system to evaluate the effects of escalating rates of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
253
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(261 citation statements)
references
References 28 publications
(31 reference statements)
5
253
1
2
Order By: Relevance
“…Under an acute imposed stretch, the axonal cytoskeleton deforms elastically when the tension is high (18). Here, the imposed stretch rate is assumed to be much higher than the possible rate of growth of the axon under an applied stretch (25). With the stretch sustained, F-actin possibly slides with respect to each other giving rise to a relaxation of the tension.…”
Section: Discussionmentioning
confidence: 99%
“…Under an acute imposed stretch, the axonal cytoskeleton deforms elastically when the tension is high (18). Here, the imposed stretch rate is assumed to be much higher than the possible rate of growth of the axon under an applied stretch (25). With the stretch sustained, F-actin possibly slides with respect to each other giving rise to a relaxation of the tension.…”
Section: Discussionmentioning
confidence: 99%
“…During development, axons may reach targets, such as the neuromuscular junction (NMJ), by mid-embryonic stages. The majority of the axon growth may later be achieved via mechanical stretch (Pfister et al 2004) as growth of the body occurs, a process independent of growth cone motility. In contrast, during regeneration, the growth cone has to traverse the entire distance and must be regulated by growth mechanisms that do not involve stretch.…”
Section: Axon Regenerationmentioning
confidence: 99%
“…33 It has also been shown that moderate tensile loads can accelerate neuronal growth, both in vitro and in vivo. [34][35][36][37][38][39] Toward the development of more effective nerve regeneration strategies, in this study, we detail the design, fabrication, and preliminary implementation of a novel internal fixator device. This modular device, by imposing mechanical loads on regenerating nerves in parallel with existing tissue engineering strategies for nerve repair, facilitates two regimes of nerve extension-traditional extension through axonal outgrowth into an engineered scaffold and novel extension of intact regions of the proximal nerve (Fig.…”
Section: Introductionmentioning
confidence: 99%